Evaluation of Hepatic Steatosis Grades with Thermoacoustic Imaging in a Rabbit Model - Xiang Hongjin, Huang Lin, Zheng Zhu, Li Jiawu, Qiu Tingting, Wu Zhenru, Shi Yujun, Jiang Huabei, Ling Wenwu, Luo Yan (Advanced Ultrasound in Diagnosis and Therapy, 2025)
Objective: Simple hepatic steatosis can no longer be ignored as a "benign finding", and the management and evaluation of the clinical interventions depend on the degree of hepatic steatosis. Here, we aimed to investigate the feasibility and diagnostic performance of thermoacoustic imaging (TAI) for assessing hepatic steatosis grades in a rabbit model. Methods: High-fat diet was used for the rabbits. To collect various degrees of hepatic steatosis, the diet duration was different (4, 8, 12, 16, 20, and 24 weeks). An in-vivo liver TAI imaging system was developed. At the end of the feed point, rabbits underwent the TAI and laparotomy for liver histopathology. Results: We performed TAI and histopathologic examinations for 33 rabbits developing none (n = 4), mild (n = 16), moderate (n = 6), and severe (n = 7) steatosis with/without hepatic fibrosis. A strong correlation was found between the thermoacoustic fat coefficient (TAFC) derived from TAI and liver fat percentage (Pearson correlation coefficient, 0.865; P < 0.001). Besides, TAFC showed significant differences between the consecutive grades of steatosis. TAI potentially provided a good diagnostic performance, with 83% sensitivity and 100% specificity for mild steatosis, 92% sensitivity and 95% specificity for moderated steatosis, and 100% sensitivity and 92% specificity for severe steatosis. The fibrosis stage did not significantly affect the TAFC. Conclusion: Our findings demonstrate that TAI is a promising way to evaluate hepatic steatosis grades.